Arsenic-induced responses in Pityrogramma calomelanos (L.) Link Arsenic speciation, mineral nutrition and antioxidant defenses - Campos, N V (Plant physiology and biochemistry : PPB, 2015)
Copyright © 2015 Elsevier Masson SAS. All rights reserved.